2013
DOI: 10.3892/ol.2013.1186
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic and apoptosis-inducing properties of a C21-steroidal glycoside isolated from the roots of Cynanchum auriculatum

Abstract: The present study aimed to investigate the anti-cancer effect of a C21-steroidal glycoside (CG) isolated from the roots of Cynanchum auriculatum. CG was able to inhibit the growth of human cancer cells (SGC-7901 cells) in a concentration and time-dependent manner in vitro. SGC-7901 cells exposed to CG (10.8 and 21.6 μM) exhibited typical morphological apoptosis characteristics, such as nuclear-chromatin condensation and apoptotic body formation. Flow cytometric analysis showed that after treatment with CG at 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Current studies have explained the anticancer activity of C. auriculatum extracts and the potential mechanisms involved [45,46]. However, caudatin, a C-21 steroid derived from C. auriculatum, has not been investigated in selective cytotoxicity against human CSCs.…”
Section: Discussionmentioning
confidence: 99%
“…Current studies have explained the anticancer activity of C. auriculatum extracts and the potential mechanisms involved [45,46]. However, caudatin, a C-21 steroid derived from C. auriculatum, has not been investigated in selective cytotoxicity against human CSCs.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from inhibition of cell proliferation, apoptosis is another important event that anticancer drugs target [ 19 ]. In the previous study, we found different C 21 -steroidal glycosides with different cytotoxicity and apoptosis inducing properties [ 20 , 21 ]. Therefore, we also explored whether the growth inhibition effect of CGII is related to apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the same and novel C21-steroidal glycosides were also detected in C. auriculatum and C. wilfordii (Li et al, 2008;Lu, Xiong, Hong, Guang, & Zhi, 2011;Xiang, Ma, & Hu, 2010;Ye, Wang, Yang, & Zhang, 2013;Zhang, Ye, Shen, & Liang, 2000). Besides, novel compounds, such as Wilfoside K1N inhibiting angiogenesis (Kim et al, 2005), cynandione A protecting from cytotoxicity (Lee et al, 2015), and amino-substituted p-benzoquinone (Yeo & Kim, 1997), were isolated from roots of C. wilfordii.…”
mentioning
confidence: 87%